It's a twin thing - "Katschke, Judy" (HarperCollinsEntertainment: London, 1999)
For Ashley, the new school year means shopping for new clothes and meeting new boys. Her twin sister, Mary-Kate, would much rather hit a softball than a mega-mall. But they do agree on one thing - they're too old for a babysitter!
Keywords: Children's stories-Fiction